First records of the exotic ant Tetramorium bicarinatum (Nylander, 1846) (Hymenoptera: Formicidae) in the Balearic Islands - Arcos, Javier; Alarcón , Francisco (Entomological Communications, 2024)
The ant Tetramorium bicarinatum (Nylander, 1846) (Hymenoptera: Formicidae) is a successful tramp species that is found in several tropical and subtropical regions throughout the world, including hundreds of islands in the Pacific, Atlantic, and Indian oceans, as well as in many Mediterranean countries. Interestingly, reports of T. bicarinatum in Mediterranean islands are yet scarce. Here we present the first two records of T. bicarinatum in the Balearic Islands.